Cardiac arrest caused by nafamostat mesilate - Hyo Shik Kim; Kyung Eun Lee; Ji Hyun Oh; Chan Sung Jung; Dughyun Choi; Yunsuek Kim; Jin Seok Jeon; Dong Cheol Han; Hyunjin Noh (The Korean Society of Nephrology, 2016)
A 65-year-old man was transferred from the Department of Vascular Surgery to Nephrology because of cardiac arrest during hemodialysis. He underwent incision and drainage for treatment of a buttock abscess. Nafamostat mesilate was used as an anticoagulant for hemodialysis to address bleeding from the incision and drainage site. Sudden cardiac arrest occurred after 15 minutes of dialysis. The patient was treated in the intensive care unit for 5 days. Continuous veno-venous hemodiafiltration was started without any anticoagulant in the intensive care unit. Conventional hemodialysis was reinitiated, and nafamostat mesilate was used again because of a small amount of continued bleeding. Ten minutes after hemodialysis, the patient complained of anaphylactic signs and symptoms such as dyspnea, hypotension, and facial swelling. Epinephrine, dexamethasone, and pheniramin were injected under the suspicion of anaphylactic shock, and the patient recovered. Total immunoglobulin E titer was high, and skin prick test revealed weak positivity for nafamostat mesilate. We first report a case of anaphylactic shock caused by nafamostat mesilate in Korea.